Ensuring Trust and Integrity: A Revolutionary Approach to Electronic Voting Through Blockchain - Misni, HM; Jokonowoa, Bambang; Santoso, Hadi (International Journal of Artificial Intelligence Research, 2023)
The voting method has recently been a subject of continuous discourse in numerous countries. Nevertheless, the utilization of electronic voting systems raises apprehensions about several security aspects, including but not limited to eligibility, anonymity, privacy, integrity, accuracy, and impartiality. This paper introduces an innovative strategy for augmenting the security and dependability of an electronic voting system by utilizing Blockchain technology. By eliminating the requirement for physical receipts, countering coercion (specifically, vote-selling), and guaranteeing universal verifiability, this approach aims to mitigate voter distrust in the government or governing body. This technology effectively upholds the principles of voter secrecy and verifiability. Election transparency is upheld through Blockchain technology, which serves as a secure repository for all voting transactions. Concurrently, individual voters' anonymity is preserved through a sophisticated procedure that integrates ring and within-blind signatures. In addition, the system has incorporated sophisticated card-based voter authentication and security procedures, which have been implemented with the assistance of the governing body and executed through the Dapp platform. This technology will provide a comprehensive solution and provide more excellent compatibility for elections conducted on a large scale.